2010
DOI: 10.4172/jcsb.1000050
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Docking Studies of 266 Compounds from 7 Plant Sources as Antihypertensive Agents

Abstract: Various proteins play important roles in hypertension and a number of plants have been tested for their efficacy in modulating hypertension. Angiotensin 1-converting enzyme, renin and extracellular regulated kinase 2(ERK2) proteins, respectively, has major role in hypertension and therefore protein -ligand interaction studies were performed on 266 compounds from different parts of 7 plants (Allium sativum, Coriandrum sativum, Dacus carota, Murrayya koneigii, Eucalyptus globus, Calendula officinalis and Lycoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…One study has revealed previously unexplored targets along with metabolites that are well established in antibiotic discovery. Identification of established metabolites strengthen our analyses while the newly discovered metabolites could lead to novel antimicrobials [52,60].…”
Section: Application To Biosciencesupporting
confidence: 55%
See 2 more Smart Citations
“…One study has revealed previously unexplored targets along with metabolites that are well established in antibiotic discovery. Identification of established metabolites strengthen our analyses while the newly discovered metabolites could lead to novel antimicrobials [52,60].…”
Section: Application To Biosciencesupporting
confidence: 55%
“…Current technology allows for comprehensive and rapid mRNA expression profiling and mass spectrophotometric measurement of low molecular weight intermediates and metabolic products. In prokaryotic organisms, this combination provides a potentially powerful tool for identifying gene function and regulatory networks even in the absence of a combined proteomic approach [32,62,63]. One of the researches has been focused on metabolites that these are essential for the growth and survival of the relevant bacteria.…”
Section: Application To Biosciencementioning
confidence: 99%
See 1 more Smart Citation
“…Lycopersicon esculentum 93 Solanaceae Fruit Moringa oleifera 94 Moringaceae Leaves Musanga cecropiodes 8 Cecropiaceae Stem bark Memordica charantia 95 Cucurbitaceae Whole plant Melothria maderaspatana 96 Cucurbitaceae Leaves Mesona procumbens 8 Lamiaceae Seed Matricaria recutita 97 Asteraceae Flower Nigella sativa 98 Ranunculaceae Seeds Oleo europpaea 1 Oleaceae Leaves Opuntia dillenii cladodes 99 Cactaceae Leaves Peganum harmala 8 Nitrariaceae ------Phyllanthus amarus 100 Euphorbiaceae Leaves Pinus pinaster 101 Pinaceae Bark Phyllanthus urinaria 102 Phyllanthaceae Fruit ,leaf ,flower Passiflora nepalensis 103 Passifloraceae Petals Panax ginseng 104 Araliaceae Root Panax quinquefolius 105 Araliaceae Root Periploca laevigata 1 Apocynaceae Bark, root Persea americana mill 106 Lauraceae Leaves Raphanus sativus 83 Cruciferae ----Rhaptopetalum coriaceum oliver 8 Scytopetalaceae Stem bark Retama raetam forssk 1 Fabaceae Leaves Sesamum indicum 8 Pedaliaceae Seeds Solanum sisymbriifolium 107 Solanaceae Root Salvia cinnabarina 1 Lamiaceae Leaves Solanum torvum 108 Solanaceae Fruits Saururus chinensis 109 Saururaceae Root Theobroma cacao 110 Malvaceae Tanacetum vulgare 111 Asteraceae Leaf Tropaeolum majus 112 Tropaeolaceae Seed, leaf ,flower Ulmus macrocarpus 1 Ulmaceae . Root bark Uncaria rhynchophylla 113 Rubiaceae ----Vitex donian 1 Verbenaceae Plant Zingiber officinale 114 Zingiberaceae Rhizome Achillea wilhemsii 115 Astreaceae Leaves, Flowers Lepeechinia caulescens 116 Lamiaceae...…”
Section: Ginko Biloba90mentioning
confidence: 99%
“…Cell-based High-Content Screening (HCS) is an upcoming technique for the investigation of cellular processes and their alteration by multiple chemical or genetic perturbations [67]. Screening methods are routinely and extensively used to reduce cost and time of drug discovery [68]. Researchers quickly discovered the urgent need of screening of eye diseases for invention of drugs [69].…”
Section: Preventive Measuresmentioning
confidence: 99%